Explosives Expert Twyla Tharp Dance at Sandler's Wells reviewed - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 2003)
Review of Twyla Tharp Dance at Sandler's Wells. PALABRAS CLAVE: Twyla Tharp, Surfer at the River Styx, The Fugue.